Structural Restoration of the Empty Nose: A Quantitative Case Report on Post-Infectious Saddle Nose Deformity Using Autologous Sixth Costal Cartilage - Made Dalika Nareswari; Agus Rudi Asthuta; Eka Putra Setiawan; I Wayan Sucipta; I Ketut Suanda (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Septal abscess represents a catastrophic failure of the nasal structural framework, often resulting in rapid ischemic necrosis of the quadrangular cartilage and a severe saddle nose deformity. This empty nose phenomenon poses unique reconstructive challenges due to the total loss of the L-strut and compromised mucosal envelope. Case presentation: We report the case of a 34-year-old female presenting with a Type IV saddle nose deformity and bilateral nasal valve collapse following a septal abscess. Preoperative assessment demonstrated a severe Nasal Obstruction Symptom Evaluation (NOSE) score of 85 out of 100 and compromised Minimum Cross-Sectional Area (MCA) on acoustic rhinometry (mean 0.365 cm2). The patient underwent open septorhinoplasty utilizing autologous sixth costal cartilage. The graft was fabricated using the concentric carving principle to create extended spreader grafts and a columellar strut, re-establishing the dorsal and caudal support. Conclusion: At the 6-month postoperative follow-up, the NOSE score improved by 82.3% (score 15 out of 100), and objective acoustic rhinometry confirmed a 54% expansion in mean MCA. Physical examination revealed a stable dorsal profile with no early evidence of graft warping or resorption. Autologous sixth costal cartilage provides the necessary biomechanical bulk and structural rigidity for restoring the post-infectious nasal skeleton, though long-term monitoring for cartilage memory remains essential.